Earlier flowering did not alter pollen limitation in an early flowering shrub under short-term experimental warming - Pan, Cheng-Chen (Sci Rep, 2017)
In animal pollinated plants, phenological shifts caused by climate change may have important ecological consequences. However, no empirical evidence exists at present on the consequences that flowering phenology shifts have on the strength of pollen limitation under experimental warming. Here, we investigated the effects of experimental warming on flowering phenology, flower density, reproductive success, and pollen limitation intensity in Caragana microphylla and evaluated whether earlier flowering phenology affected plant reproduction and the level of pollen limitation using warmed and unwarmed open top chambers in the Horqin Sandy Land of Inner Mongolia, northern China. The results of this study indicated that artificial warming markedly advanced flower phenology rather than extending the duration of the flowering. Additionally, warming was found to significantly reduce flower density which led to seed production reduction, since there were insignificant effects observed on fruit set and seed number per fruit. Experimental floral manipulations showed that warming did not affect pollen limitation. These results revealed the negative effects of advanced phenology induced by warming on flower density and reproductive output, as well as the neutral effects on reproductive success and pollen limitation intensity of long surviving plants.